Aid and policy preference in oil-rich countries: Comparing Indonesia and Nigeria - Ahmad Helmy Fuady (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper analyses the role of foreign aid to assist development in two oil-rich countries: Indonesia and Nigeria. This paper seeks to understand the way foreign aid provided assistance to transform Indonesia from a 'fragile' state in the 1960s into one of the 'Asian Tigers' in the mid-1990s, and why it did not prevent Nigeria from falling into 'African Tragedy'. This paper argues that foreign aid could help not only to finance development, but also to navigate policy makers' policy choices. It shows how foreign aid could or could not help policy makers turn their policy preferences into action.
Keywords: O13; O19; O57; H63; 330; aid; fragile state; policy; oil; Indonesia; Nigeria